Religious Extremism in the Former Soviet Union - A. V. Vinokur (Евразийская интеграция: экономика, право, политика)
The article is devoted to judgment of the concept “religious extremism”, its diffusion in the Former Soviet Union, to implication forms and references on counteraction. Religious extremism is the difficult social phenomenon, which affects the political, legal and moral sphere. Based on the analysis of modern publications and actual data, the author shows that successful preventive activities for counteraction to religious extremism in the Former Soviet Union require a combination of legislative and technical restrictions of extremist orientation information dissemination.